Development in Venezuela of energy system based in the hydrogen. I: Production of electrolytic hydrogen - Posso, Fausto (Rev. Téc. Fac. Ing. Univ. Zulia, 2010)
We study the viability of the first stage of the development of the Energetic System Solar-Hydrogen in Venezuela, by means of the construction and manipulation of a mathematical model of the production cost of H2. The H2 is produced by electrolysis of water, with the hydroelectricity as the primary source, and will destined to satisfy the energy needs of the rural sector inhabitants. The model is applied for three case studies. The results show that the production cost increase in the lapse of the simulation, whereas when the increases the H2 production in the same year, the production costs and the electrolyser cost diminished, both behaviors by effect of the scale economy. One concludes that the development of first stage energetic system proposed is viable and advantageous.